Influence of Bloodmeal Host on Blood Feeding, Egg Production, and Offspring Sex Ratio of Ctenocephalides felis felis (Siphonaptera: Pulicidae). Issue 4 (22nd April 2016) - Yiguan, Wang; Jie, Tian; Qiyong, Liu; Cannan, Shi; Wenlong, Kai; Henglu, Duan; Cheng, Xu; Wenzhu, Zhang; Fajun, Chen; Fengxia, Meng
Abstract: The cat flea, Ctenocephalides felis felis (Bouché), feeds on different host species, causing annoyance or transmitting disease agents. In this study, the influence of the host of the cat flea on blood feeding, egg production, and sex ratio of the offspring was investigated. Two strains of C. felis were domesticated on either rats or mice for >10 yr in the laboratory, and in this study, these fleas were placed in the following groups and fed on rats or mice continuously: Group A (rat-domesticated C. felis with rats as host); Group B (rat-domesticated C. felis with mice as host); Group C (mouse-domesticated C. felis with rats as host); and Group D (mouse-domesticated C. felis with mice as host). In total, 240 adult fleas were in each group at a sex ratio of female:male = 1.7:1. The mean egg production per flea of Groups A, B, C, and D was 55.0, 19.2, 62.5, and 13.2, respectively. A significant correlation between egg production and the volume of blood consumed was detected for Groups A, B, C, and D. The sex ratio (F:M) of the offspring in Groups A and C was 2.07 and 2.11, respectively, whereas in Groups B and D, the ratio was 1.04 and 1.03, respectively. In conclusion, the C. felis with rats as host consumed more blood, produced more eggs, and had higher sex ratios of the offspring than those with mice as the host.